Історія становлення й розвитку вітчизняного інституту адміністративної юстиції - Бевзенко, В.; Bevzenko, V. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
У статті зроблено спробу висвітлити основні віхи й особливості формування та розвитку вітчизняного інституту адміністративної юстиції. Зауважено, що українська адміністративна юстиція має багатовіковий досвід функціонування, на неї вплинуло перебування етнічних земель України в складі інших державних утворень. Зроблено висновок, що український інститут адміністративної юстиції перебував переважно під впливом неукраїнської державно-політичної ідеології. Історію цього інституту розглянуто як із національних, так і наднаціональних позицій; доведено, що запровадженню адміністративної юстиції на українських землях передували непрості історичні, політичні, міжнаціональні, суспільні передумови. In the given article an attempt to highlight the key stages and peculiarities of formation and development of the national Institute of administrative justices is done. It is noted that the Ukrainian administrative justice has a centuries-old experience. It has been affected by the staying of ethnic Ukrainian lands in the part of other state formations. The Ukrainian Institute of administrative justice was mainly under the influence of non-Ukrainian state political ideology. History of this institute is examined as from national and supranational perspectives. It is proved that the not simple historical, political, international, social conditions preceded the introduction of administrative justice on Ukrainian lands. It is proved that the process of the formation of national administrative justice can be divided into seven main periods: 1) judicial system and legal proceedings in the Ukrainian lands in the Grand Duchy of Lithuania; 2) judicial system and legal proceedings of Hetman’s era; 3) administrative justice in the Ukrainian lands during the period of the Russian and Austro-Hungarian empires; 4) administrative justice during the times of formation of Ukrainian statehood; 5) formation of administrative justice by representatives of the Government of the Ukrainian National Republic in exile (1920–1992); 6) administrative justice of Ukraine since her stay in the USSR (1920–1990); 7) the newest administrative justice of Ukraine (since 1990).
The History of Formation and Development of the National Institute of Administrative Justice
Keywords: адміністративна юстиція; Україна; інститут; administrative justice; Ukraine; Institute